1990
DOI: 10.1182/blood.v75.1.284.bloodjournal751284
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte membrane inhibitor of reactive lysis: effects of phosphatidylinositol-specific phospholipase C on the isolated and cell- associated protein

Abstract: The erythrocyte membrane inhibitor of reactive lysis (MIRL) is an 18-Kd protein that controls complement-mediated hemolysis by restricting the activity of the membrane attack complex. MIRL expression on the erythrocytes of paroxysmal nocturnal hemoglobinuria (PNH) is abnormally low, and the greater susceptibility of PNH erythrocytes to complement is causally related to this deficiency. Inasmuch as other proteins that are deficient in PNH are anchored to the membrane through a glycosyl phosphatidylinositol moie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0
3

Year Published

1991
1991
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 0 publications
3
7
0
3
Order By: Relevance
“…The reason in their studies Ibr the apparent discrepancy between the PI-PLC-sensilivities of in situ and purified CD59 protein is unclear, but selective loss of unacylated molecules during purification couid lead lo a higher proportion of molecules with aeylaled GPI-anchors in the latter case. Our observation that PI-PLC-cleaved CD59 molecules exhibit decreased SDS-PAGE mobility can also account for previous observations [25] that (i) MIRL released from erythrocytes by the en/yme displayed a slightly greater apparent A/r ihan MIRL immunoprecipitated from intact celis, whereas (ii) when isolated, Pl-PLC-treated MIRL showed the same apparent Mr as untreated MIRL. Previous findings that GPl-anchor removal from VSGs.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The reason in their studies Ibr the apparent discrepancy between the PI-PLC-sensilivities of in situ and purified CD59 protein is unclear, but selective loss of unacylated molecules during purification couid lead lo a higher proportion of molecules with aeylaled GPI-anchors in the latter case. Our observation that PI-PLC-cleaved CD59 molecules exhibit decreased SDS-PAGE mobility can also account for previous observations [25] that (i) MIRL released from erythrocytes by the en/yme displayed a slightly greater apparent A/r ihan MIRL immunoprecipitated from intact celis, whereas (ii) when isolated, Pl-PLC-treated MIRL showed the same apparent Mr as untreated MIRL. Previous findings that GPl-anchor removal from VSGs.…”
Section: Discussionsupporting
confidence: 89%
“…acylalion accounts for the previously reported variability in CD59's PI-PLC sensitivity. Our finding thai 84 90% of CD59 molecules in erythrocytes contain GPI-anchors that exhibit acylation can additionally explain observations by Ilolguin et al [25] that PI-PLC treatment of purified erythrocyte MIRLdid not prevent its incorporation into PNH erylhrocytes or alter its ability to inhibit C9 polymerization in the reconstituted PNH cells. The reason in their studies Ibr the apparent discrepancy between the PI-PLC-sensilivities of in situ and purified CD59 protein is unclear, but selective loss of unacylated molecules during purification couid lead lo a higher proportion of molecules with aeylaled GPI-anchors in the latter case.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Further, it was shown that by using an antibody to block the function of MIRL, normal erythrocytes could be rendered susceptible to CVFBb-initiated hemolysis. As anticipated, PNH erythrocytes were found to be deficient in MIRL Subsequent studies showed that MIRL also belongs to the family of GPI-linked proteins (38).…”
Section: Membrane Inhibitor Of Reactive Lysis (Mirl Cd59)supporting
confidence: 55%
“…In this report we describe a schistosome C inhibitory protein type I (SCIP-1) that is a 94-kD protein functionally and antigenically related to human CD59. We demonstrate that several properties of CD59, such as the capacity to inhibit formation of C MAC and the binding of human C8 and C9 components (23,29,30) are manifested by SCIP-1 as well, and that both molecules are, apparently, external glycosyl phosphatidylinositol-anchored membrane proteins (31). Furthermore, antibodies directed to human CD59 bind to SCIP-1 and render the parasite susceptible to C-mediated killing.…”
mentioning
confidence: 87%